Online Car Repair Shop Application with Android-Based Home Service - Leonardus Alexandri Damiato; Wahyu Sri Utami (Publikasi Indonesia, 2024)
The use of private cars has reached a total of 23,230,297 units. The number of car users, either for delivering goods, means of transportation, or for personal interests makes it easier for drivers to carry out their activities. Mobile vehicles have their way of keeping the car in good condition, such as automatic car services and clutch cars with different ways of handling. Car accidents cannot be separated from problems when traveling, for example, tires leaking due to punctured nails, crashing tires, and accidents stuck in holes. The limited number of people who know the location of the nearest workshop to the current location can cause confusion and have to ask people around from the workshop needed and there are still many motorists who have not been able to take good care of their cars Current technological developments I propose an online workshop application so that instead of asking people around it will be easier if from a smartphone you can bring the workshop itself to the location or the house, People can order home service services so that it is easier for people to check the car from home.